Dispersion of Thermo Elastic Waves in a Rotating Cylindrical Panel - Rajendran Selvamani; P. Ponnusamy (International Journal of Advances in Applied Sciences, 2013)
The three dimensional dispersion of thermo elastic waves in a homogeneous isotropic rotating cylindrical   panel is investigated in the context of the linear theory of thermo elasticity. Three displacement potential functions are introduced to uncouple the equations of motion. The frequency equations are obtained using the traction free boundary conditions. The Bessel function with complex argument is directly used to analyze the frequency equations. The analysis of thermally induced vibration of rotating cylindrical panel is common place in the design of structures, atomic reactors, steam turbines, supersonic aircraft, and other devices operating at elevated temperature. In order to illustrate theoretical development, numerical solutions are obtained and presented graphically for a zinc material .To compare the model with the exiting literature, the non dimensional frequencies for different thickness to inner radius ratio are computed and  they show very good agreement.